Avaliação da genotoxicidade de Cichla melaniae no Rio Xingu em ambientes impactados pela Usina Hidrelétrica de Belo Monte - CORREIA, Leticia Lima (2022)
Under increase of human population, the use of nonrenewable resources has been broadly used. The hydroelectric power plants building, the rise up native forests deforestation for timber resources, cattle beef grazing and agribusiness are causing serious environmental troubles, such as the Global Warming intensification and water resources pollution. The hydroelectric dams building not only in the Amazon, but also in other sites around the world causes troubles due to the reservoir formation, rivers and lakes eutrophication as well as ease the bioaccumulation and biomagnification at native species. Thus, the target of this Academic Study is analyzing the exposure of Cichla melaniae (tucunaré) at four collection points, inside and outside the Belo Monte Hydroelectric Power Plant reservoir over possible damage by environmental contamination. It was analyzed through micronucleus (MN) test 1000 erythrocytes per fish, with 100x magnification under an optical microscope, the slides were stained with 5% Giemsa. Among the collection points there was no significant difference for the NM test. For the nuclear anomalies, it was not possible to observe many variations among the collection points, but the point VG1 presented a greater variation for invagination, compared to the other points. Revealing that areas under the influence of Hydroelectric, Gold Mining and Agriculture can have changes in their ecosystem and cause genotoxic effects on native species.